Virtuella stängsel för getter (Capra hircus) - Reimeskog, Malin (2020)
There are currently about 20,000 goats in Sweden. In a survey on goat farming by the Swedish Board of Agriculture, it was discovered that goat farmers often perceive the enclosure of goats as problematic. There is a growing interest in virtual fencing in Sweden, which offers a solution to fence off animals without the work of setting up physical fences. Instead, virtual fences use necklaces, which give a warning signal and electric shock when the animal approaches a virtual boarder. The necklaces are connected to GPS or a cable on the ground that determines the enclosure boundaries. NoFence is a virtual fence currently allowed for use on goats in Norway. The Swedish Board of Agriculture has taken part of two studies on NoFence but deemed that the studies did not meet the standard of animal welfare in Sweden. It is, at this time, not allowed to use electrical equipment to control animal behavior in Sweden, but the Swedish Board of Agriculture can provide exceptions to this law.